Overview of Pneumonia Prevention Efforts in Toddlers Aged 2–59 Months at the MTBS Polyclinic: Overview of Pneumonia Prevention Efforts - Soplestuny, Maryati; Fajar, Harianti (CV. Paperhome Indonesia, 2025)
Background: Pneumonia is one of the most common lung infections and a leading cause of death among children under five. One of the main causative agents is Streptococcus pneumoniae. Prevention of pneumonia can be carried out through simple interventions, particularly by parents, such as the implementation of clean and healthy living behaviors (PHBS). Methods: This study used a quantitative approach with a descriptive design. A total of 114 parents of toddlers aged 2–59 months who visited the MTBS (Integrated Management of Childhood Illness) polyclinic at Tawiri Community Health Center were selected using purposive sampling. Results: The results showed that more than half of the respondents (55.3%) did not practice proper handwashing with soap. Most of the children (98.2%) were exposed to poor household air quality, and the majority of respondents (93.9%) did not implement correct coughing etiquette. Conclusion: Pneumonia prevention efforts among toddlers aged 2–59 months at the MTBS polyclinic of Tawiri Community Health Center were not optimal. It is recommended that the health center intensify health education for parents and community health workers regarding pneumonia prevention in toddlers.